2020
DOI: 10.1021/acs.jpclett.0c00087
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nature of Nuclear Magnetic Resonance Relaxation by Means of Fast-Field-Cycling Relaxometry and Molecular Dynamics Simulations—The Validity of Relaxation Models

Abstract: Fast-field-cycling relaxometry is a nuclear magnetic resonance method growing in popularity; yet, theoretical interpretation is limited to analytical models of uncertain accuracy. We present the first study calculating fast-field-cycling dipolar coupling directly from a molecular dynamics simulation trajectory. In principle, the frequency-resolved dispersion contains both rotational and translational diffusion information, among others. The present joint experimental/molecular dynamics study demonstrates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 25 publications
2
45
1
Order By: Relevance
“…The one applied in this work, however, has already proven to reproduce experimental NMR results. 35 The reasonable agreement with the experimental values validates the accuracy of the MD simulation; thus the computational NOE calculations can be used to decompose observable sum spectra into different components. We dissect σ L (ν) into contributions from spin pairs at different distances, The 1 H− 19 F contributions converge at larger distances than 1 H− 7 Li contributions, meaning the latter are barely affected by spin interactions with the bulk.…”
supporting
confidence: 65%
“…The one applied in this work, however, has already proven to reproduce experimental NMR results. 35 The reasonable agreement with the experimental values validates the accuracy of the MD simulation; thus the computational NOE calculations can be used to decompose observable sum spectra into different components. We dissect σ L (ν) into contributions from spin pairs at different distances, The 1 H− 19 F contributions converge at larger distances than 1 H− 7 Li contributions, meaning the latter are barely affected by spin interactions with the bulk.…”
supporting
confidence: 65%
“…The discussion above evidenced that the choice of the right FFC NMR model to apply to soils and soil related materials is left to investigator's sensibility. However, very recently, a new study dealing with the combination between FFC NMR modeling and molecular dynamics (MD) simulations appeared [78]. The authors showed that NMRD profiles and temperature trends can be calculated with a very good approximation by using MD simulations.…”
Section: The Ffc Nmr Modeling Via Molecular Dynamics Simulationsmentioning
confidence: 99%
“…While a few picoseconds-long trajectory had to suffice for Lipari and Szabo's [74] seminal work on the 'model-free’ approach, today, calculations beyond the millisecond scale are feasible on desktop computers [49] . Indeed, relaxation parameters bear the potential to elucidate structure–function relationships by assessing protein motions, and with the help of MD simulations, such information can be supplemented with structural models [75] , [76] .…”
Section: Combining Nmr and MD Simulationsmentioning
confidence: 99%